Pelaksanaan Perilaku Sehat pada Anak Usia Dini Di Paud Thalabul Ilmi Kabupaten Maros Implementation Of Healthy Behavior in Early Childhood at PAUD Thalabul Ilmi Maros Regency - Suriati Arif Damang (Jurnal Komunitas Kesehatan Masyarakat, 2022)
The Application of concept of healthy behavior must start from an early age, and optimal childgrowth and development depends on the healthy bevahior carried out, eventhough earlychildhood can not be given learning like children’s learning in general schools with structcurrikulum and discipline but habituation through observation and intervention, healthybehavior that is the focus of research and observed in this study is behavior eating and drinking,behavior towards personal hygiene, behavior toward environmental hygiene, balance behaviorand behavior toward illness/disease. This study aims to describe the healthy behavior of earlychildhood in PAUD Thalabul Ilmi Maros Regency, Province South Sulawesias a recommendationto PAUD Thalabul Ilmi Maros institutions so that they can be followed up. Because the success ofPAUD institutions in carring out their role as partners, parents should educated about healthybehavior for early childhood and become a second place for habituation of these healthybehaviors. This study use the descriptive method with a survey method, carried out throughdirect questionnaires to 50 parents/guardians of PAUD Thalabul Ilmi Maros. The results showedthat the healthy behavior of early childhood in PAUD Thalabul Ilmi Maros had not beenimplemented properly by students, this was indicated by behavior that was in sufficient criteriaincluding enviromntel hygiene behavior 36%, behavior illness and disease 58 % and balancebehavior (sleep and activity needs) 36%, while eating and drinking behavior 69%, behaviortowards personal hygiene 69% in a good criteria. Conclusion implementation of healty behaviorat Early childhood PAUD Thalabul Ilmi Maros is not implemented properly, recommended thereneed to be more cooperation between school and parents in shaping the behavior of earlychildhood.